PERBANDINGAN PELAMPUNG BATANG DAN PELAMPUNG PUNGGUNG TERHADAP KETERAMPILAN RENANG GAYA PUNGGUNG - Ishak , Mochamad; Hasmarita, Sony; Pristiawati, Ani (STKIP Pasundan, 2019)
The objectives of this study are: (1) Determine the effect of trunk buoys on backstroke swimming skills (2) Determine the effect of back buoys on backstroke swimming skills (3) Knowing which is more influential between rod buoys and back buoys on backstroke swimming skills in Kampoeng learn swimming club. In this study the authors used the experimental method by trying out a treatment to find out how much influence it had on the object it was holding. The population used in this study was the Kampoeng students learning swimming clubs, amounting to 104 students, while the sample used was 28 people from students who were not proficient in backstroke swimming with a sampling technique using purposive sampling. From the calculation results it can be seen that the average difference between pre-test and post-test occurred significantly in the experimental group (stem buoy users) 34.00 while the average control group (back buoy user) 36.00 for backstroke swimming skills. Calculation results t comparison of the differences in the two learning outcomes 2.133 smaller than t Table 2.158. Thus we can reject the hypothesis (Ho), then it can be concluded that: Back buoy media is more influential on backstroke swimming skills compared to stem buoys